Degradation mechanism of 2-fluoropropene by Cl atoms: experimental and theoretical products distribution studies. Issue 8 (11th February 2022) - Rivela, Cynthia B.; L. Cardona, Alejandro; Blanco, María B.; Barnes, Ian; Kieninger, Martina; Ventura, Oscar N.; Teruel, Mariano A.
Abstract : Gas-phase reaction products of 2-fluoropropene with Cl atoms have been determined for the first time at 298 K and atmospheric pressure using a 1080 L quartz-glass photoreactor coupled with in situ FTIR spectroscopy to monitor reactants and products. Abstract : The gas-phase reaction products of 2-fluoropropene (2FP) with Cl atoms have been determined for the first time at 298 K and atmospheric pressure using a 1080 L quartz-glass photoreactor coupled with in situ FTIR spectroscopy to monitor reactants and products. Acetyl fluoride and formyl chloride were observed as the main products with yields of (106 ± 10)% and (100 ± 11)%, respectively. Electronic structure calculations of reactants, intermediates, products and transition states on a detailed mechanism of the reaction were performed by DFT procedures (BMK, M06, M062X/D3), as well as accurate composite methods on both the addition and abstraction reaction channels. From the joint experimental and theoretical studies, we concluded that the reaction occurs primarily via addition to the Cα carbon, with a smaller participation of the addition on the Cβ carbon, which is not produced directly from the separated reactants but from the CH3 CFCH2 Cl intermediate radical through a submerged transition state. The abstraction channel occurs at larger energies than the addition ones, and also presents a submerged transition state, with a lower barrier. No products arising from this channel are expected. The proposed mechanism explains also why formaldehyde, predicted as a product by former theoretical studies, is not found among the experimental products. The atmospheric implications of the reaction products are assessed.